Effects of Colombia's Social Protection System on Workers' Choice between Formal and Informal Employment - Camacho, Adriana; Conover, Emily; Hoyos, Alejandro (Oxford University Press on behalf of the World Bank, 2016)
We examine whether the Colombian government's expansion of social programs in the early 1990s, particularly the publicly provided health insurance, discouraged formal employment. Using household survey data and variation across municipalities in the onset of interviews for the SISBEN, the instrument used to identify beneficiaries for public health insurance, we find robust and consistent estimates of an increase in informal employment of approximately 4 percentage points. We find similar results using an alternative dataset, consisting of a panel of individuals interviewed for the first and second SISBEN. Our findings suggest that marginal individuals optimized when deciding whether to participate in the formal sector.